What can EMU countries' sovereign bond spreads tell us about market perceptions of default probabilities during the recent financial crisis? - Niko Dötz; Christoph Fischer (Deutsche Bundesbank, 2010)
This paper presents a new approach for analysing the recent development of EMU sovereign bond spreads. Based on a GARCH-in-mean model originally used in the exchange rate target zone literature, spreads are decomposed into a risk premium, an expected loss component and a liquidity premium. Time-varying default probabilities are derived. The results suggest that the rise in sovereign spreads during the recent financial crisis mainly reflects an increased expected loss component. In addition, the rescue of Bear Stearns in March 2008 seems to mark a change in market perceptions of sovereign bond risk. The government bonds of some countries lost their former role as a safe haven. While price competitiveness always helps to explain sovereign spreads, it increasingly moved into investors' focus as financial sector soundness weakened.
Keywords: E43; G15; C32; H63; F36; 330; Sovereign bond spread; GARCH-in-mean; default probability; Öffentliche Anleihe; Zinsstruktur; Kreditrisiko; Risikoprämie; Schätzung; ARCH-Modell; Europäische Wirtschafts- und Währungsunion; Eurozone